GEOLOGY AND PETROGRAPHY OF THE VEDEL ISLANDS (WILHELM ARCHIPELAGO, WEST ANTARCTICA) - Mytrokhyn, O.; Bakhmutov, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The Vedel Islands are a small island group that is part of the Wilhelm archipelago in the West Antarctica. They are located near the Graham Coast of the Antarctic Peninsula at a distance of 12 km from Akademik Vernadsky Ukrainian Antarctic Station. Until recently, the Vedel Islands were a "white spot" on all existing geological maps. In 2019, during the seasonal work of the 24th Ukrainian Antarctic expedition, the authors first carried out field geological researches on the Vedel Islands. The main goal of the geological survey was reconnaissance and large-scale geological mapping. The general ideas about the geological structure of the study area were developed by further processing of the collected materials. The preliminary data about the mode of occurrence, the geological ages, the petrographic peculiarities and the ore potential of the local rocks were also obtained. It was first established that multiple-aged intrusive-magmatic formations take part in the geological structure of the Vedel Islands. The intermediate compositions of the plutonic rocks namely the diorites and quartz diorites are the most common among them. The gabbroids and the tonalites are less common. The least common ones are hypabyssal and subvolcanic dike rocks namely microdiorites and diabases. The plutonic rocks were formed in at least three intrusive phases with a homodromous order of their intrusions. The most ancient among them are gabbroids. The Early Cretaceous age for their formation is assumed by analogy with the petrographically similar rocks of the Tuxen-Rasmussen layered gabbroid intrusion (TRGI). The tonilites are the youngest plutonic rocks on the Vedel Islands. It is assumed that their formation at a deep level took place in the Late Cretaceous, although their tectonic exhumation and the final erosion outcropping occurred in the Paleogene and ended in the Neogene. In the process of the exhumation, the plutonic rocks were intruded by hypabyssal dikes of microdiorites. The youngest subvolcanic diabase dykes intruded the tonalites supposedly after their complete erosion outcropping i. e. in Neogene or even Quaternary. Like TRGI and other layered gabbroid intrusions of the Wilhelm archipelago, the Vedel island gabbroids contain iron-titanium oxide-ore and copper-silicate mineralization, which requires further study. The additional researches are also needed to clarify the age, origin, petrography and mineralogy of the numerous veins of aplite-pegmatoid granite which intrude gabbroids and diorites on the Vedel Islands.
Keywords: Antarctic Peninsula; Graham Coast; Wilhelm archipelago; geology; petrography